If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 6a + -2(a + -3) = -12 Reorder the terms: 6a + -2(-3 + a) = -12 6a + (-3 * -2 + a * -2) = -12 6a + (6 + -2a) = -12 Reorder the terms: 6 + 6a + -2a = -12 Combine like terms: 6a + -2a = 4a 6 + 4a = -12 Solving 6 + 4a = -12 Solving for variable 'a'. Move all terms containing a to the left, all other terms to the right. Add '-6' to each side of the equation. 6 + -6 + 4a = -12 + -6 Combine like terms: 6 + -6 = 0 0 + 4a = -12 + -6 4a = -12 + -6 Combine like terms: -12 + -6 = -18 4a = -18 Divide each side by '4'. a = -4.5 Simplifying a = -4.5
| 19=-3k-5 | | 4(1)-7y=15 | | 3x-4=2-4 | | 3(x+7)+2=2x+2(3x-1) | | 7p-36=-4(-6p-8) | | 6-4+5*11= | | -2u^2-7u-5=0 | | -3(5-b)= | | 2(-2x+4)=-8 | | 4x^3+13x^2+4x-12=0 | | -6x+7x+6=18 | | 2(+3)+4s-5+s=148 | | 4(5+4)-10=2(9+f)-6 | | 12x-4=5x+66 | | 4(x+5)-6=6x-2(-5+x) | | 4(4-t)-(3-2t)=9 | | 75x+150=-3 | | -8x-136=4x+80 | | 3.2y-1.33=-y+4.13 | | -2(x+6)=-2(x-6) | | 254.687+1.91+1= | | -1.5+.75=-.75 | | -32x+25x=-43 | | -6x+9+7x=3+x+6 | | -3(6)-5=-23 | | 4n+22=3n+11 | | 7ln(5-x)=6 | | 6+3(x-4)=5(x-1)+1 | | 3+(3-x)=x+5 | | 25+25+x=180 | | 6-30= | | (2x)+(20y-10)=360 |